The Relationship among Internet Addiction, Moral Potency, Mindfulness, and Psychological Capital - Girum Tareke Zewude; Tun Zaw Oo; Gabriella Józsa; Krisztián Józsa (MDPI AG, 2024)
This research aimed to contribute to the literature on internet addiction (IA) and moral development among university students. Moral potency (MP) encompasses the interconnected dimensions of moral courage, moral ownership, and moral efficacy. Studies on the relationships between students' problematic behaviors (e.g., IA) and cognitive processes like MP, mindfulness (MI), and psychological capital (PsyCap) are scarce in educational research. Therefore, this study investigated the relationships among IA, MP, MI, and PsyCap in university students. This study included 868 undergraduate students from a state university in Ethiopia, with 526 male students (60.6%) and 342 female students (39.4%). Participants' ages ranged from 21 to 29 years, with a mean age of 22.31 and a standard deviation of 4.03. The findings indicated that IA was negatively correlated with MI, PsyCap, and MP. Both MI and PsyCap showed positive correlations with MP. Importantly, this study revealed that IA had a direct and negative impact on MI, PsyCap, and MP. Further, MI and PsyCap partially mediated and fully mediated the relationship between IA and MP. These findings suggest that cultivating MI and positive PsyCap among university students could be an important strategy to reduce the risks of IA and enhance their moral development. This study contributes to the limited research on the complex relationships between technology use, psychological resources, and moral functioning in emerging adulthood.